Identifying the Resistant Bacterial Pattern in Patients with Diabetic Foot Ulcer - Ali, Sura Qusay; Kamil, Yasir Majid (Journal for Research in Applied Sciences and Biotechnology, 2022)
Background: Diabetes is a term used to describe a group of metabolic disorders that are hyperglycemic due to deficiencies in insulin secretion, insulin action, or both. Diabetes complications are common in both type 1 and type 2 diabetes patients, and they are responsible for significant morbidity and mortality. One of the persistent diabetes complications is a foot ulcer associated with neuropathy. These ulcers eventually lead to infections in the diabetic foot. Diabetic foot diseases such as ulceration, gangrene, Charcot joint, and fracture are common causes of amputation. Methodology: The study was conducted of 23 samples from foot ulcers diabetic disease. Relevant clinical, biochemical, and microbiological sensitivity evaluations were carried out on the subjects. Results: This study has shown that the highest ratio of isolated bacteria from diabetic foot ulcer patients were Staphylococcus aureus, Pseudomonas aeruginosa and Streptococcus pyogenes respectively. The isolated Gram-positive bacteria were more than isolated gram-negative bacteria. Both Streptococcus pyogenes and Staphylococcus aureus showed a high resistance to Benzylpenicillin and Oxacillin, Whereas some isolates of Pseudomonas aeruginosa showed resistance to Imipenem, meropenem and Piperacillin/Tazobactam. Escherichia coli were resistant to Ticarcillin, Aztreonam, Cefepime and Ceftazidime. Klebsiella pneumoniae show high resistant to all of antibiotics. Proteus mirabilis resist to Aztreonam, Cefepime, Ceftazidime, Gentamicin, meropenem, Piperacillin/ Tazobactam, Trimethoprim/ Sulfamethoxazole and Tobramycin. Conclusion: The outcome of current study has shown that the isolated Gram-positive bacteria were more than isolated gram-negative bacteria in foot ulcer patients, with different pattern of resistance to the studied antibiotics.